A study of the interfacial resistive switching mechanism by proton exchange reactions on the SiOx layer. Issue 2 (14th December 2015) - Zhou, Fei; Chang, Yao-Feng; Chen, Ying-Chen; Wu, Xiaohan; Zhang, Ye; Fowler, Burt; Lee, Jack C.
Abstract : Localized oxygen deficiency in the "GAP" region facilitated the proton exchange reactions in the SiO x layer and reproducible memory switching at 180 °C. Abstract : In this work, we investigated SiO x -based interfacial resistive switching in planar metal–insulator–metal structures using physical/chemical/electrical analyses. This work helps clarify the interfacial reaction process and mechanism in SiO x, and also shows the potential for high temperature operation in future nonvolatile memory applications.